PdO nanoparticles supported on triazole functionalized porous triazine polymer as an efficient heterogeneous catalyst for carbonylation of aryl halides. (21st June 2019) - Sadhasivam, Velu; Balasaravanan, Rajendran; Siva, Ayyanar
Abstract : A well‐defined triazole functionalized porous triazine based polymers act as solid heterogeneous catalyst after incorporating palladium oxide nanoparticles (PdO@TTAS) have been synthesized and thoroughly characterized by various techniques such as, FT‐IR, UV‐DRS, solid state 13 C CP‐MAS, XPS, powder X‐ray diffraction, TGA, SEM and TEM analysis has been detailed illustrated. It is important to note that synthesized catalytic performance for carbonylation of aryl halides (X = I, Br) with EDC.HCl ( N ‐(3‐dimethylaminopropyl)‐N′‐ethylcarbodiimide hydrochloride), and formic acid was found to be an effective CO source in the presence of triethylamine as a base and DMF as a solvent medium at 80 °C for about 3 hr. The PdO@TTAS catalyst exhibits superior catalytic performance and along with good yield (up to 90%). Moreover, studying the heterogeneity and reusability of the environmentally friendly solid catalyst can be easily separated by simple filtration and then recycled for several times. In this reaction method, we avoided ligand, additive, promoters and CO gas, due to additional problem arise by using gaseous CO, highly toxic greenhouse gases and high pressurized reaction setup. Abstract : A new type of palladium oxide nanoparticles incorporated triazole functionalized porous triazine based polymer act as solid heterogeneous catalyst for carbonylation of aryl halides with EDC.HCl and formic acid act as an effective CO source in the presence of triethylamine and DMF solvent medium. The PdO@TTAS catalyst exhibits superior catalytic performance and along with good yield (up to 90%).